Hubungan Antara Perbedaan Beban Trauma Dengan Gambaran Histopatologi Inflamasi Otak Tikus Pasca Mengalami Cedera Otak Traumatik: Relationship Between Differences In Trauma Load With Histopathological Description Of Rat Brain Inflammation Post Traumatic Brain Injury - Muzakki Hasnan Ali; Rohadi Rohadi; Lale Maulin Prihatina; Zikrul Haikal (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Brain injury is a damage to the brain, not congenital or degenerative, but caused by an attack or physical impact from the outside. Traumatic brain injury (TBI) is an injury that occurs when a force transmitted to the head or body causes neuropathological damage and dysfunction. TBI is one of the most common head injuries worldwide. This disorder affects 2% of the world's population each year and is the leading cause of death and serious disability in children and young adults. Getting hit or bumped into objects, motor vehicle crashes and falls, and intentional self-injury are the most common causes of TBI. This study aims to determine the histopathological description of brain inflammation in post-traumatic brain injury rats and analyze the relationship between differences in trauma burden and histopathological features of brain inflammation in post-traumatic brain injury rats. This research is an experimental study conducted by giving treatment to the object under study and then observing it. Sampling in this research will use purposive sampling. Where the researcher has determined the criteria of the sample to be used in the study so that it can represent the population. The results of this study indicate that there is a relationship between differences in trauma load and the percentage of rat brain inflammation after experiencing traumatic brain injury. The results of data analysis from this study for the Pearson test obtained a significance value of 0.00 so that there is a correlation between differences in trauma load and the percentage of brain cell inflammation in rats after experiencing traumatic brain injury. The Pearson correlation value of this data is 0.7621 which means a strong correlation. The results showed a significant inflammatory picture compared to the histopathological appearance of rat brain cells in normal samples.